2022
DOI: 10.1111/adb.13168
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between impulsivity and MDPV self‐administration in rats

Abstract: Synthetic cathinones, such as 3,4-methylenedioxypyrovalerone (MDPV), are recreational drugs of abuse often identified in 'bath salts' preparations. Humans report compulsive patterns of bath salts use, and previous work suggests that a subset of rats develop unusually high levels of MDPV self-administration. This study aims to test the hypothesis that high levels of impulsivity (e.g., inability to withhold responding for a sucrose reward) will predispose rats to high levels of MDPV self-administration relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 65 publications
(103 reference statements)
3
10
0
Order By: Relevance
“…When allowed to self-administer the stimulant drug MDPV, a subset rats rapidly develop patterns of responding that result in significantly greater levels of drug-intake (high-responders) than low-responder rats self-administering MDPV, or rats that self-administer cocaine. These high-responder rats exhibit behaviors thought to be consistent with stimulant use disorder in humans, including high levels of drug-taking and -seeking, and reach higher final ratios under progressive ratio schedules of reinforcement (Gannon et al, 2017;Doyle et al, 2021a;Abbott et al, 2022). The primary goal of this study was to evaluate the effects of several drugs that interact with receptors that have been targeted for the development of medications for stimulant use disorder to determine if their potency and effectiveness to reduce drug-taking differed as a function of: (1) the self-administered drug (MDPV versus cocaine), ( 2) the behavioral phenotype (high-responder versus low-responder), or (3) sex (male versus female).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When allowed to self-administer the stimulant drug MDPV, a subset rats rapidly develop patterns of responding that result in significantly greater levels of drug-intake (high-responders) than low-responder rats self-administering MDPV, or rats that self-administer cocaine. These high-responder rats exhibit behaviors thought to be consistent with stimulant use disorder in humans, including high levels of drug-taking and -seeking, and reach higher final ratios under progressive ratio schedules of reinforcement (Gannon et al, 2017;Doyle et al, 2021a;Abbott et al, 2022). The primary goal of this study was to evaluate the effects of several drugs that interact with receptors that have been targeted for the development of medications for stimulant use disorder to determine if their potency and effectiveness to reduce drug-taking differed as a function of: (1) the self-administered drug (MDPV versus cocaine), ( 2) the behavioral phenotype (high-responder versus low-responder), or (3) sex (male versus female).…”
Section: Discussionmentioning
confidence: 99%
“…Rats were subsequently classified as being a high-or low-responder based upon previously established criteria (Gannon et al, 2017(Gannon et al, , 2018aDoyle et al, 2021a;Abbott et al, 2022). Briefly, the percentage of responses that were made during the 5-sec post-infusion timeout out of total responses on the active lever in drug components was calculated for the 3 sessions preceding the final saline substitution.…”
Section: Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying rats with more extreme phenotypes may provide a more translational framework to understand factors that underlie the transition from regular to disordered patterns of substance use. Though a relatively small subset of rats (17-22%) develop the most severe SUD-like phenotype when they are allowed to self-administer cocaine [3,8], a much larger proportion of rats (~30-40%) engage in aberrantly high levels of drug-taking when MDPV is available for self-administration [25][26][27][28][29]. Thus, the primary goals of the current studies were to directly compare the SUD-like phenotype in male and female rats self-administering MDPV or cocaine, and to determine how manipulating access condition (short-, long-, and intermittent-access) impacted these SUD-like phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…3,4-methylenedioxypyrovalerone (MDPV) is a synthetic cathinone that functions as a cocaine-like monoamine uptake inhibitor, but unlike cocaine which is roughly equipotent at the dopamine, norepinephrine, and serotonin transporters (DAT, NET, and SERT, respectively) MDPV is ~800-fold selective for DAT and NET over SERT [22][23][24]. We have previously reported that 30-40% of male and female rats that are allowed to selfadminister MDPV during daily 90-min sessions rapidly develop a high-responder phenotype, characterized by levels of MDPV intake ~2-5 times greater than lowresponders across a range of doses, greater breakpoints under progressive ratio schedules of reinforcement, and higher rates of responding during periods of signaled drug unavailability [25][26][27][28][29]. Though consistent with MDPV high-responder rats engaging in SUD-like behaviors, it is unclear if the phenotype observed in these rats would extend to other core SUD-related behaviors, such as resistance to punishment by footshock, (i.e., "continued use despite adverse consequences"), or if the "severity" of the SUD-like phenotype is sensitive to access condition manipulations, as has been reported for cocaine.…”
Section: Introductionmentioning
confidence: 99%